Functional diversity patterns reveal different elevations shaping Himalayan amphibian assemblages, highlighting the importance of morphologically extreme individuals. (June 2023) - Zhao, Tian; Su, Guohuan; Jiang, Jianping; Li, Na; Zhao, Chunlin; Sun, Zijian; Khatiwada, Janak Raj
Graphical abstract: Highlights: Amphibian functional diversity differed between elevational zonations. Amphibian functional distinctiveness existed across elevational zonations. Functional diversity was largely contributed by a few functionally extreme amphibians. Functional vulnerability of amphibian assemblages existed throughout all the zonations. High elevational area should be in particular well protected to maintain amphibian functional diversity. Abstract: Biological diversity is a concept that contains multiple facets, of which functional diversity is considered to be more integrative to describe the relationship between biodiversity and ecosystem functioning. In recent decades, functional diversity patterns have been assessed along elevational gradients in plants and birds. However, few empirical studies have been conducted to reveal amphibian functional diversity patterns between elevational zonations on mountains. In the present study, we investigated amphibian ecomorphologically functional diversity patterns in different elevational zonations of Nepal Himalaya. Our results indicated that functional space occupied by amphibian assemblages differed in size between elevational zonations, with assemblages in zonation-2 (500–1300 m) occupying the highest proportion. In terms of the position in functional space, assemblages in low elevational zonations (zonation 1 & 2) differed significantly from those in high elevational zonations (zonation 3–5). Distribution of individuals in the five assemblages along the six axes of the functional space was significantly different between most pairs of comparisons, while the difference varied between assemblages along axes. Interestingly, despite morphologically extreme amphibians accounted for small proportions of the total number of amphibians, they filled a large proportion of the six dimensional functional space. More importantly, most of the extreme amphibians were also the most functional uniqueness individuals, and they were widely distributed in all the zonations. Therefore, functional vulnerability of amphibian assemblages exists throughout all the elevational zonations. Accordingly, extreme amphibians with most functional uniqueness should be in particular well protected to maintain amphibian functional diversity. Further research can explore the mechanism underlying the unique amphibian functional diversity patterns in Nepal Himalaya.